2021
DOI: 10.1002/prp2.819
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of medicinal plants and phytochemicals on chemotherapy‐induced neuropathic pain through glial modulation

Abstract: Chemotherapy‐induced peripheral neuropathy (CIPN) frequently occurs in cancer patients. This side effect lowers the quality of life of patients and may cause the patients to abandon chemotherapy. Several medications (e.g., duloxetine and gabapentin) are recommended as remedies to treat CIPN; however, usage of these drugs is limited because of low efficacy or side effects such as dizziness, nausea, somnolence, and vomiting. From ancient East Asia, the decoction of medicinal herbal formulas or single herbs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…The genus Trichosanthes is mainly distributed in eastern and southern Asia in warm and moist habitats [47,55]. As a medicinal use, it has been known that different parts of the plant, such as the fruit, root, and seed, have different efficacies [31]. In this study, the root tuber of Tk was used, which has been reported to have a treatment effect against diabetes [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Trichosanthes is mainly distributed in eastern and southern Asia in warm and moist habitats [47,55]. As a medicinal use, it has been known that different parts of the plant, such as the fruit, root, and seed, have different efficacies [31]. In this study, the root tuber of Tk was used, which has been reported to have a treatment effect against diabetes [56].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the analgesic effect of bee venom, morphine, and herbal medicines [22,[26][27][28][29]. Among them, we focused on various herbal medicines, since herbal medicines are mostly known to be relatively safe and to induce only a low occurrence of side effects compared to other chemically modified drugs [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism involves glial activation [ 21 , 39 , 40 ]. For example, the myelin sheath can be damaged by chemotherapeutic agents.…”
Section: Peripheral and Spinal Mechanisms Of The Cipnmentioning
confidence: 99%
“…In fact, although being considered as an neuropathic pain, current pharmacological treatments for this condition (tricyclic antidepressants, anticonvulsants, etc.) are slightly effective in CIPN or have undesirable reactions (Hou et al, 2018), such as dizziness, nausea, somnolence and vomiting (Lee et al, 2021).…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%
“…In this sense, the development of neuropathies is the most recurrent cause for alteration of chemotherapy regimens, leading to a decrease in dose and frequency or choice of a different therapeutic agent, leading to impairments to the treatment and a lower quality of life ( Lee et al, 2021 ). Unfortunately, there are no sufficient options available for the CIPN treatment ( Colvin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%